Altered Neural Activity in the Mesoaccumbens Pathway Underlies Impaired Social Reward Processing in Shank3‐Deficient Rats - Marie Barbier; Keerthi Thirtamara Rajamani; Shai Netser; Shlomo Wagner; Hala Harony‐Nicolas (Advanced Science)
Abstract Social behaviors are crucial for human connection and belonging, often impacted by conditions like Autism Spectrum Disorder (ASD). The mesoaccumbens pathway (ventral tegmental area (VTA) to the nucleus accumbense (NAc)) plays a pivotal role in social behavior and is implicated in ASD. However, the impact of ASD‐related mutations on social reward processing remains insufficiently explored. This study focuses on the Shank3 mutation, associated with a rare genetic condition and linked to ASD, examining its influence on the mesoaccumbens pathway during behavior, using the Shank3‐deficient rat model. Our findings indicate that Shank3‐deficient rats exhibit atypical social interactions, associated with altered neuronal activity of VTA dopaminergic and GABAergic neurons and reduced dopamine release in the NAc. Moreover, they demonstrate that manipulating VTA neuronal activity can normalize this behavior, providing insights into the effects of Shank3 mutations on social reward processing  and identifying a potential neural pathway for intervention.